Guillain-Barré syndrome in a child with COVID-19 associated multi system inflammatory syndrome - Erubothu, Alekhya; Rudrappa, Sudha; Patagar, Pratibha Manjunath (International Journal of Contemporary Pediatrics, 2021)
Multi-system inflammatory syndrome in children (MIS-C) associated with SARS-CoV-2 is a new entity affecting a small percentage of children during the COVID-19 pandemic. This usually presents with multi-organ dysfunction, predominantly affecting cardiovascular, muco-cutaneous, and gastrointestinal systems. Till now, neurological manifestations as a part of this spectrum, such as, encephalopathy, inflammatory CNS syndromes, cerebrovascular disease, and Guillain-Barré syndrome (GBS), have been well reported in adults, but there is a paucity of data from the paediatric age group. Here, we present a case of a 6-year-old girl who presented to us with progressive, bilaterally symmetrical ascending weakness of lower limbs followed by upper limbs along with drooling of saliva and dyspnea. Nerve conduction studies showed motor axonal neuropathy suggestive of GBS and child was treated accordingly with intravenous immunoglobulin. On 4th day of admission, the child developed high grade fever spikes, hypotension and diarrhoea. Hence, worked up for MIS-C which revealed elevated inflammatory markers with positive SARS-CoV-19 IgM, IgG antibodies. The diagnosis was hence revised to GBS with MIS-C, the child was then started on methylprednisolone following which the child showed both clinical and biochemical improvement and was then discharged. A high index of suspicion for the possibility of MIS-C should be kept in mind in the present pandemic times, as the immune-mediated damages in MIS-C are potentially treatable with a timely institution of intensive care measures along with the use of steroids, IV-Ig, and plasmapheresis.